Emergence of novel strains ofShigella flexneriassociated with sexual transmission in adult men in England, 2019‐2020. Issue 10 (October 2021) - Dallman, Timothy J; Charles, Hannah; Prochazka, Mateo; Sinka, Katy; Hughes, Gwenda; Godbole, Gauri; Jenkins, Claire
Abstract : N/A: National surveillance of shigellosis in England revealed an increase in sexually transmitted Shigella flexneri in adult males in 2019 that persisted throughout 2020. We observed a resurgence of azithromycin‐resistant S. flexneri serotype 3a, and the emergence of two novel multidrug‐resistant clades of S. flexneri 2a and S. flexneri 1b.